The everyday competitive mothering of tourists: global tourism competition, homestays, and mothering labour - Becklake, Sarah (Globalizations, 2024)
Global tourism competition has entered home and family space. Drawing upon ethnographic research in Guatemala, this paper investigates the postcolonial gendered politics that shape (and are shaped by) global tourism competition, homestays, and mothering labour. It shows how Guatemalan women turn to hosting as an economic strategy and, in doing so, become part of a complex power relationship between Spanish schools and their (primarily Western) language tourists (or 'students'). Spanish schools only work with 'host-mums' deemed capable of meeting their students' needs, desires, and expectations of homestays as affordable, enjoyable, pedagogical experiences of 'real' family. To achieve this, Guatemalan women become cosmopolitan, competitive subjects who devise and enact strategies to commodify, transform, and perform their mothering labour and homes/families in ways that appeal to their Western students. Far beyond creating desirable touristic experiences, the everyday competitive mothering of tourists is having widespread consequences at the personal, local, and global levels.